Evaluation of pulmonary artery wall properties in congenital heart disease patients using cardiac magnetic resonance. (December 2017) - D'Souza, Gavin A.; Taylor, Michael D.; Banerjee, Rupak K.
Abstract: Congenital heart disease patients (CHD) with complex right heart disease are often left with residual lesions that result in right ventricular (RV)-pulmonary artery (PA) dysfunction post surgery. The appropriate timing of re-intervention to correct these lesions is difficult to determine due to lack of suitable quantifiable diagnostic techniques. The PA wall (material) properties characterize the mechanical behavior of the PAs and thus, contribute significantly to the RV-PA function. Therefore, the arterial wall properties of the main PA (MPA), left PA (LPA), and right PA (RPA) of three CHD subjects with normal RV-PA function and anatomy were quantified using retrospective pressure-diameter data as input to a constitutive (material) model. Intra-vessel (MPA vs branched PAs) and inter-subject variability was observed in the wall properties and consequently, the arterial wall compliance and stress-stretch characteristics. The LPA was least compliant in comparison to the MPA and RPA. Also, the circumferential and axial stress in the PAs increased with the subject's age. Therefore, monitoring the wall properties of the individual PAs may provide valuable longitudinal (time-dependent) information on disease progression of CHD patients. Highlights: The main, left, and right pulmonary artery (PA) wall properties of congenital heart disease patients are assessed. In vivo pressure and diameter are obtained using cardiac catheterization and cardiac MRI, respectively. A 2D nonlinear hyperelastic material model is used in conjunction with the in vivo data to predict the PA wall properties. Intra-vessel and inter-subject variability observed in the wall properties, compliance, and stress-stretch characteristics.